2015
DOI: 10.1016/j.apjtm.2015.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Natural products: Perspectives in the pharmacological treatment of gastrointestinal anisakiasis

Abstract: This study shows that some natural products exhibited promising antianisakis properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 29 publications
(33 reference statements)
2
29
0
Order By: Relevance
“…In vivo assays on larvae of A. simplex showed that LD 50 EOs ranged from 9.5 to 46.9 mg in a carrier of 0.5 mL of olive oil caused the dead of all larvae in the gastric cavity of rats (Valero et al, 2015). However, studies in vivo with EOs has been not performed with regard to larvae of Anisakis or other …”
Section: In Vitro Activity Of Essential Oils On Fish Parasitesmentioning
confidence: 99%
See 4 more Smart Citations
“…In vivo assays on larvae of A. simplex showed that LD 50 EOs ranged from 9.5 to 46.9 mg in a carrier of 0.5 mL of olive oil caused the dead of all larvae in the gastric cavity of rats (Valero et al, 2015). However, studies in vivo with EOs has been not performed with regard to larvae of Anisakis or other …”
Section: In Vitro Activity Of Essential Oils On Fish Parasitesmentioning
confidence: 99%
“…Many of these bioactive molecules are found at low concentrations (less than 1%), while a few of them are major compounds that can represent up to 70% of the total volume of oil and are mainly responsible for the bioactive effects of the EO (Bakkali et al, 2008;Cunha et al, 2017). Several of these secondary metabolites of medicinal plants present diverse antiparasitic activity (Bakkali et al, 2008;Soares and Tavares-Dias, 2013;Romero et al, 2014, Valero et al, 2015Hashimoto et al, 2016, Soares et al, 2016Sharifi-Rad et al, 2017).…”
Section: Secondary Metabolites Of Plants and Essential Oilsmentioning
confidence: 99%
See 3 more Smart Citations